Extreme heat and cardiovascular mortality among structurally marginalized populations in the United States: A scoping review - Cory Sejo; Natasha Mehta; Samantha Wilairat; Michele Barry; Michelle C. Odden; Andrew Y. Chang (The Journal of Climate Change and Health)
Introduction: Extreme heat and heat waves have long been recognized as a significant risk factor for cardiovascular disease exacerbations and death. Differential outcomes among structurally marginalized populations are less well understood, and in particular, the impact of this environmental hazard on cardiac mortality deserves further exploration for these populations. Methods: A scoping review was conducted to characterize the scientific literature examining the impact of extreme heat on cardiovascular mortality among structurally marginalized populations in the United States. Using relevant medical subject headings (MeSH) and key terms, a systematic search of the indexing databases of Pubmed, Embase, and Web of Science for English-language manuscripts published from inception to July 2023 for primary research, systematic reviews, meta analyses, and narrative reviews was performed. Results: 4674 articles were screened, of which 33 which met inclusion criteria. The majority (73 %) of these were primary quantitative research studies, all of which were observational in nature. Half of the research designs were cohort studies. The most common marginalized group described was that of older adults (79 % of manuscripts), while race/ethnicity (42 %), sex/gender (42 %), and lower socioeconomic status (49 %) were also commonly explored. Most studies assessed aggregated composite cardiovascular mortality as the primary end point, with only four fractionating myocardial ischemia/infarction as the cause of death. Conclusions: Future directions of study for the field include additional analyses of other marginalized groups including differently-abled, immigrant, outdoor laborers, incarcerated peoples, Hispanic/Latinx, Native American, and Asian American/Pacific Islander populations, as well as determining the impact of diverse socioeconomic parameters, and examining disaggregated cardiac outcomes.